The need for continued monitoring of antibiotic resistance patterns in clinical isolates of Staphylococcus aureus from London and Malta - Easmon Sue; Hilton Anthony C; Rollason Jess; Cuschieri Paul; Gould Simon WJ; Fielder Mark D (BMC, 2010)
Abstract Background Antibiotic resistance is an increasing problem in isolates of Staphylococcus aureus (S. aureus) worldwide. In 2001 The National Health Service in the UK introduced a mandatory bacteraemia surveillance scheme for the reporting of S. aureus and methicillin-resistant S. aureus (MRSA). This surveillance initiative reports on the percentage of isolates that are methicillin resistant. However, resistance to other antibiotics is not currently reported and therefore the scale of emerging resistance is currently unclear in the UK. In this study, multiple antibiotic resistance (MAR) profiles against fourteen antimicrobial drugs were investigated for 705 isolates of S. aureus collected from two European study sites in the UK (London) and Malta. Results All isolates were susceptible to linezolid, teicoplanin and vancomycin. Multiple antibiotic resistance profiles from both countries were determined, a total of forty-two and forty-five profiles were seen in the UK cohort (MRSA and MSSA respectively) and comparatively, sixty-two and fifty-two profiles were shown in the Maltese group. The largest MAR profile contained six antibiotics (penicillin G, methicillin, erythromycin, ciprofloxacin, clindamycin and clarithromycin) and was observed in the MRSA isolates in both the UK and Maltese cohorts. Conclusion The data presented here suggests that the monitoring of changing resistance profiles locally in maintaining treatment efficacy to resistant pathogens.